Die grosse Edgar Wallace Krimi-Collection - Wallace, Edgar 1875-1932; Wallace, Edgar 1875-1932 (Pidax Film- und Hörspielverlag, 2024)
A disgraced ex-RAF pilot is enlisted into a smuggling scheme by an electronically sophisticated smuggler, who has a room full of computers and recording devices. The pilot is to take stolen diamonds from across the Channel, but he plans a carefully crafted double cross instead. [www.imdb.de]
Fernsehfilm. Großbritannien. 1969
Keywords: Fernsehserie; DVD-Video